Dental Implants Analysis by Means of Video Image Correlation Method. (2015) - Szava, Daniel-Tamas; Bogozi, Balint; Galfi, Botond-Pal; Szava, Ioan; Ionescu, Raluca Dora; Munteanu, Renata Ildiko
Abstract: In this contribution, the authors are offering useful details on a non-contact, experimental investigation tool, namely: the VIC-3D optical system. The facilities of this system are allowing its implementation in the dental practice, more exactly in the dental implants optimization from stress-strain state point of view. They describe an original testing bench, destined to evaluate the strain-field in the vicinity of the dental implants mounted in some artificial mandibles, obtained by Rapid Prototyping. Finally, there are illustrated the experimental approach facilities by mean of some preliminary results.